Risk Factors for Falls Among Older Adults: Implications for Preventing Geriatric Syndrome-Related Emergencies - Nugrahaeni Firdausi; Widhi Sumirat (STIKES Adi Husada, 2026)
Increasing life expectancy in Indonesia has led to a growing older adult population and a higher prevalence of fall-related geriatric syndromes. This study aimed to identify factors associated with falls among older adults to support fall prevention. This study employed an analytical observational study with a cross-sectional design to identify factors associated with falls among older adults. The dependent variable was the incidence of falls, whereas the independent variables included age, sex, physical function, cognitive function, psychological status, balance, mobility, muscle strength, disease history, lighting conditions, floor conditions, use of walking aids, and polypharmacy. Data were analyzed using Spearman's rank correlation test to determine the relationships between the study variables. The study population consisted of older adults residing at UPT Pelayanan Sosial Tresna Werdha Jombang, Kediri. Thirty-one participants who met the eligibility criteria were recruited. The statistical analysis of the respondents' data showed that psychological status, physical function, and mobility were significantly associated with the incidence of falls among older adults. The analysis revealed that psychological status (p = 0.037), physical function (p = 0.045), and mobility (p = 0.031) were significantly associated with the incidence of falls among older adults. Psychological status, physical function, and mobility are significant determinants of falls among older adults. Early identification of these risk factors and implementation of comprehensive fall-prevention strategies by healthcare professionals may reduce geriatric syndrome-related emergencies, decrease morbidity and mortality, and improve the quality of life of older adults.